Effects of Spironolactone on Dialysis Patients With Refractory Hypertension: A Randomized Controlled Study. Issue 9 (22nd July 2014) - Ni, Xiaoying; Zhang, Jisheng; Zhang, Ping; Wu, Fuquan; Xia, Min; Ying, Guanghui; Chen, Jianghua
<x xml:space="preserve">Abstract</x> The purpose of this study was to evaluate the effects of spironolactone on dialysis patients with refractory hypertension and possible adverse effects. This was a 12‐week prospective, randomized, double‐blind trial of 82 patients randomly assigned to 12‐week treatment with 25 mg/d spironolactone or placebo as add‐on therapy. Visits were scheduled at the start of treatment and after 12 weeks. Measurements of 24‐hour ambulatory blood pressure (BP) monitoring and morning BP were performed. After 12 weeks, spironolactone significantly improved refractory hypertension. Average placebo‐corrected morning BP was reduced by 16.7/7.6 mm Hg. Mean 24‐hour ambulatory BP was reduced by 10.9/5.8 mm Hg. In contrast, serum aldosterone levels in the spironolactone group slightly increased and serum potassium levels insignificantly increased. This study has demonstrated that spironolactone (50 mg) safely and effectively reduces BP in patients with refractory hypertension undergoing dialysis.